Which factors affect the live birth outcome of the first single euploid frozen-thawed blastocyst transfer in couples with balanced chromosomal translocations? - Zhang, Ruixiao; Hu, Yahui; Cui, Chenchen; Zhang, Cuilian (Frontiers in Endocrinology, 2024)
Objective: The objective of this study is to investigate the factors that influence the live birth rate (LBR) of the first single euploid frozen-thawed blastocyst transfer (FBT) cycles after preimplantation genetic testing for structural rearrangements (PGT-SR) in couples with balanced chromosomal translocations (BCT).Design: Single center, retrospective and observational study.Methods: A total of 336 PGT-SR and the first single euploid FBT cycles between July 2016 and December 2022 were included in this study. The patients were divided into two groups according to the live birth outcomes. The parameters of the study population, controlled ovarian stimulation cycles, and FBT cycles were analyzed.Multivariable binary logistic regression was performed to find the factors that affected the LBR.Results: The percentage of blastocysts at developmental stage Day 5 compared to Day 6 (51.8% vs. 30.8%; P﹤0.001) and with morphology ≥BB compared to ﹤BB (49.7% vs. 32.2%; P=0.001) was significantly different between the group that resulted in live births (n=193) and the group that did not (n=143). The results of the multivariable binary logistic regression analysis indicated that the developmental stage (adjusted OR: 2.068, 95%CI 1.291-3.313; P=0.003) and morphology (adjusted OR: 1.697, 95%CI 1.039-2.773; P=0.035) of the blastocyst were significantly correlated with live birth. Patients with blastocysts that reached the developmental stage at Day 5 and had a morphology of ≥BB had a higher likelihood of having a live birth.The developmental stage and morphology of blastocyst affect the live birth outcome of the first single euploid FBT in BCT carriers undergoing PGT-SR.